PENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN MINYAK OLES BOKASHI - Wistyasari, Ni Putu; Sri Ardani, I Gst Agung Ketut (E-Jurnal Manajemen; Vol 4 No 5 (2015), 2015)
Competition in today's business is a challenge for employers to remain in the global competition. Integrated marketing strategy is the promotion mix strategy through advertising, sales promotion and personal selling. The research objective was to determine the influence of advertising, personal selling and sales promotion on product purchasing decisions Bokashi at PT. Pak Oles tokcer in Denpasar. The total sample of 120 respondens, data collection is done through questionnaires. Techniques Analysis is multiple linear regression analysis. Based on the analysis found that is, advertising, personal selling and sales promotion of positive and significant effect on purchasing product decisions Bokashi at PT. Pak Oles tokcer in Denpasar.
Keywords: Advertising, Personal Selling, Sales Promotion and Purchasing Decisions